Ur-fascism in the cultural situation after postmodern: Ukrainian and Russian context - Yevheniia Bilchenko (Cхід)
The article deals with phenomenological analysis of semantic structures of ur-fascism as a phenomenon of the totalitarian mind. The main methodological guidelines of intentional analysis of ur-fascism are the categories: archetype, symbol, world view, mentality and identity. In the article the basic principles of Eternal Fascism in postmodern aesthetics are given with the current of contemporary cultural context (monism, populist elitism, militarism, leaderism, traditionalism, xenophobia). Author of article stresses the principle of fear of Alien as an enemy, mechanisms of simulation of image of which in modern media are the simulation and reduction. The mechanisms of spread of ur-fascism are classified by the playing of variable groups (abc bcd cde def), which singled out four models of identity inUkrainenow (liberal, conservative, conservative radical, modern).